Answer:
12X+10
Step-by-step explanation:
It's easy. Just combine like terms. Like terms must have the same variable and to the same power in this case all the terms have a power of 1, but it doesnt show it because it doesn't really matter. So 4x,6x, and 2x all have the same variable so add them together. That gets you 10x. Since nothing else in the expression has the same variable with 10, you leave the 10 at the end resolving in 12x+10
1:0.05
I think this is the answer
Midpoint= in the middle
Midpoint is D
Answer:
![x>-2](https://tex.z-dn.net/?f=x%3E-2)
Step-by-step explanation:
We will need to solve the inequality:
–3x – 4 < 2
Before starting we need to understand 1 rule of inequalities. That is:
We change the inequality sign whenever we multiply or divide by a negative number. That means
< changes to >
and
≥ change to ≤
and vice versa...
Now, let's go ahead and solve the inequality:
![-3x-4](https://tex.z-dn.net/?f=-3x-4%3C2%5C%5C-3x%3C2%2B4%5C%5C-3x%3C6%5C%5Cx%3E%5Cfrac%7B6%7D%7B-3%7D%5C%5Cx%3E-2)
"x" is the set of all values that is greater than "-2". So that's the answer.
x > -2
Answer:
15 equation: 195=105+6x
Step-by-step explanation:
he starts out with 105 and the rate of change is 6x so to get the answer u wanna make and equation (195=105+6x) then you would subtract the 105
195=105+6x
-105 -105
---------------------
90=0 +6x
then u would divide by 6
90/6=6x/6
x=15